2008
DOI: 10.1111/j.1440-1827.2008.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic invasion according to D2‐40 immunostaining is a strong predictor of nodal metastasis in superficial squamous cell carcinoma of the esophagus: Algorithm for risk of nodal metastasis based on lymphatic invasion

Abstract: In squamous cell carcinoma (SCC) of the esophagus, D2-40 immunostaining has recently been used to detect lymphatic invasion, but invasion detected using D2-40 immunostaining for a predictor of nodal metastasis was controversial. Therefore, the usefulness of detecting lymphatic invasion by D2-40 immunostaining as a predictor of nodal metastasis was examined in superficial (mucosal and submucosal) SCC of the esophagus. A total of 115 superficial SCC of the esophagus were examined on immunohistochemistry using D2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 13 publications
(18 reference statements)
3
34
1
1
Order By: Relevance
“…This is in accordance with studies investigating a risk factor predictive of nodal involvement in colorectal, vulvar and esophageal cancer [11,21,26]. Our observations indicate that the main source of lymph node metastasis may be delivered from the lymphatic invasion in esophageal cancer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in accordance with studies investigating a risk factor predictive of nodal involvement in colorectal, vulvar and esophageal cancer [11,21,26]. Our observations indicate that the main source of lymph node metastasis may be delivered from the lymphatic invasion in esophageal cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Tomita et al [26] obtained similar results. Lymph node metastasis was significantly (p < 0.001) related with the tissue status of lymphatic invasion, which were diagnosed by D2-40 immunohistochemistry.…”
Section: Discussionsupporting
confidence: 76%
“…D2-40, a specific marker for lymphatic epithelium has been shown to detect lymphatic infiltration occurring in association with subepithelial extension in superficial squamous cell carcinoma of the esophagus [15]. Moreover, lymphatic infiltration according to D2-40 immunostaining was a strong predictor of nodal metastasis in superficial squamous cell carcinoma of the esophagus [16].…”
Section: Introductionmentioning
confidence: 98%
“…Lin et al [22] have reported similar observations for colorectal cancer. Imamura et al [17], Tomita et al [18] and our earlier study [23] revealed that LVI in the entire tumor tissue of esophageal cancer was significantly linked with nodal metastasis. In contrast, Mori et al [15] found that only ptLVI positively correlated with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, Mori et al [15] did not find any correlation between LVD and pathological parameters. High itLVD was found to be significantly correlated with lymph node metastasis by Inoue et al [16] and Imamura et al [17] in esophageal cancer, and by Tomita et al [18] only in subepithelial extension of esophageal cancer. A recent study suggested that intratumoral lymphatics play a greater role than peritumoral lymphatics in nodal metastasis of head and neck cancer [19].…”
Section: Discussionmentioning
confidence: 92%